In-situ experimental study of CO2 gasification of char particles on molten slag surface. (15th November 2015) - Shen, Zhongjie; Liang, Qinfeng; Xu, Jianliang; Zhang, Binbin; Liu, Haifeng
Highlights: The gasification process of char with CO2 on the molten slag surface was observed. Time for carbon conversion on slag was nearly half of the results without slag. Reaction of chars on molten slag had a higher temperature and reactivity index. The heat transfer of molten slag mainly promoted the gasification reaction of char. Abstract: In an entrained-flow gasifier, the captured char particles, which were prolonged the residence time on the molten slag surface, continued to react with the gaseous reactant and affected the carbon conversion of a gasifier. In this paper, we applied a high temperature stage microscope (HTSM) and an ImageJ software to study the gasification characteristics of char particles with CO2 on the molten slag. The results showed that the gasification reaction of char particles on the molten slag was promoted significantly, compared to the original char gasification. The section area of chars on the molten slag surface shrank obviously, and the time for the complete carbon conversion on slag was nearly the half of the results without slag. A high value of reactivity index was measured for the char samples on the molten slag. The heat transfer interactions between the slag and the char lead to a high particle temperature on the molten slag. The heat transfer rate between the slag and the char particle was dominant for the promotion of the endothermic reaction.